An investigation of the intention to leave or stay of health care professionals at St. Andrews Hospital - Amanambu, Rochelle Aneeta (Rhodes University, Faculty of Commerce, Rhodes Business School, 2014)
Background: The demand for and retention of talent worldwide is aggravated by revolutionary trends that include global competition, demographic changes and technological advances. In South Africa this phenomenon according to Frost (2002) is further challenged by the emigration of skilled people; the relative scarcity of specialist and managerial employees; employment equity and affirmative action procedures. But the development of strategies first requires an understanding of the factors which influence decisions to leave or stay particularly in rural and remote areas. St. Andrews Hospital is a rural district hospital in Ugu District, KZN. Its remoteness from urban areas and the lack of resources contributes towards challenges of attracting and retaining health care professionals to the area. It is the aim of this study to identify the ten most prevalent turnover and retention factors in a rural district hospital with the intention of making recommendations towards strategies to mitigate turnover and improve retention of health care professionals. This study will not only serve the local Human Resource Department but may also be used to inform district and provincial policies as well as departments' decisions in the design or the review of current retention strategies aimed at reducing turnover. Method: The survey method was used to collect the primary data by distribution of self-administered questionnaires to Health Care Professionals at St. Andrews Hospital. Of the one hundred and fifty questionnaires distributed, one hundred and seven were returned (71% response rate) and formed the basis of the study. Results: Based on the impact scores, the top three turnover factors identified were, the way the organisation is led by top management (0.934); the size of the workload (0.862); and the way problems are dealt with by managers in the organisation (0.817). No statistically significant relationships were found between turnover factors and biographical variable. Availability of quality health services was ranked as the external factor that had the highest influence (78%) on turnover, while geographical location was ranked the lowest. The main reason given by respondents for leaving their previous employment was promotion, followed by distance and personal/family reasons. The top three retention factors identified from the impact scores were the quality of relationships with colleagues (1.698); the amount of support received from managers and colleagues (1.484); and the level of engagement and involvement with the job (1.390). This demonstrates that the salary package often thought to be a first priority factor Mobley, Horner and Hollingsworth (1978); Mobley (1982) and Herzberg (2003) is far less of a determining factor at St. Andrews Hospital than management support, job involvement and person-organisation fit as well as the social relationships formed in the workplace. A positive relationship was found between leadership and job dimension factors at the 1% level of significance. This supports the strong social bond (person-organisation fit) formed in the work environment between management and colleagues that supports retention and increases level of commitment. An important result of the study was that 46% of the respondents were thinking of leaving the town within the year while 29% were considering resigning from St. Andrews Hospital within the year. Conclusion: The results reveal a complex interaction of factors impacting on turnover and retention. The Human Resource Management function has a pivotal role to play in improving its ability to attract and retain professionals through developing comprehensive strategies based on external and internal and environmental factors. The study conveys to the St. Andrews Hospital management that turnover and retention factors are unique to the location and the working environment and differs amongst Health Care Professionals "“ this should be deliberated on when formulating Hospital Human Resource retention policies.
Keywords: Medical personnel -- Job satisfaction -- South Africa -- Eastern Cape -- Case studies; Medical personnel -- Job stress -- South Africa -- Eastern Cape -- Case studies; Hospitals -- South Africa -- Eastern Cape -- Administration; Hospitals -- Medical staff -- South Africa -- Eastern Cape; Hospitals -- Officials and employees -- South Africa -- Eastern Cape -- Turnover; Health services administration -- South Africa -- Eastern Cape; Health planning -- South Africa -- Eastern Cape